2010
DOI: 10.1074/jbc.m110.110957
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Tau at Thr212, Thr231, and Ser262 Combined Causes Neurodegeneration

Abstract: Abnormal hyperphosphorylation of the microtubule-associated protein Tau is a hallmark of Alzheimer disease and related diseases called tauopathies. As yet, the exact mechanism by which this pathology causes neurodegeneration is not understood. The present study provides direct evidence that Tau abnormal hyperphosphorylation causes its aggregation, breakdown of the microtubule network, and cell death and identifies phosphorylation sites involved in neurotoxicity. We generated pseudophosphorylated Tau proteins b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 61 publications
(54 reference statements)
6
158
0
1
Order By: Relevance
“…We have shown that phosphorylation of tau is suffi cient to promote tau self-assembly into fi laments [29] and that phosphorylation at Ser 199 and 262 and Thr 212 and 231 is sufficient to convert tau into an D-like protein in cells [101] and in vivo in transgenic Drosophila [126] . On the basis of our results and the evidence reviewed here, we propose that the hyperphosphorylation of tau leads to neurodegeneration through microtubule disruption and the consequent decreases in neurotransmission a n d a x o p l a s m i c t r a n s p o r t ( F i g .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have shown that phosphorylation of tau is suffi cient to promote tau self-assembly into fi laments [29] and that phosphorylation at Ser 199 and 262 and Thr 212 and 231 is sufficient to convert tau into an D-like protein in cells [101] and in vivo in transgenic Drosophila [126] . On the basis of our results and the evidence reviewed here, we propose that the hyperphosphorylation of tau leads to neurodegeneration through microtubule disruption and the consequent decreases in neurotransmission a n d a x o p l a s m i c t r a n s p o r t ( F i g .…”
Section: Discussionmentioning
confidence: 96%
“…1 ) . B e s i d e s t h e microtubule disruption, we have evidence that abnormal tau translocates into the nucleus [101] and also impacts mitochondrial health in neurons. The consequences of these facts deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This MAP2 region is similar to an FBW7 phosphodegron of Tau (Thr231 and Ser235 [underlined in the above sequence]), which is modified in cooperation with GSK3. Although phosphorylation was originally reported to inhibit the microtubule-binding ability of Tau, more recent research suggests that modification of these sites may not be sufficient to induce Tau dissociation from microtubules (354,355). The phosphorylation of the latter motif may still contribute to neurotoxicity and filament forming when Tau is released from microtubules in Alzheimer's disease (355).…”
Section: Lesser-understood Jnk-dependent Phospho-switchesmentioning
confidence: 99%
“…Furthermore, as JNK2 does not display any preference (245). e In addition, Tau can be subjected to more complex regulation (354,355).…”
Section: The Many Substrates Of Jnk: 20 Years and Still Counting Subsmentioning
confidence: 99%